EFFECTS OF NEW 1st, 2nd, 3rd TRIAZOLE PRODUCTS ON BIOCHEMICAL INDICATORS OF BLOOD PLASMA AND ACTIVITY OF LIVER ANTIOXIDANT IN DIABETES CAUSED BY ALLOXAN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study established the effect of new derivatives of TF-25, TS-27, and ISO-31-triazoles on the activity of triglycerides, total cholesterol, the hormone insulin and the antioxidant enzyme superoxide dismutase (SOD), catalase in rat liver homogenate in diabetes mellitus caused by alloxan, and also on the amount of MDА, the product of lipid peroxidation.Studies were performed on male, white, breedless rats weighing 190–210 g. A solution of alloxan monohydrate (150 mg/kg) was used to create a diabetes model in rats. The experimental animals were divided into five groups. New TF-25 (40 mg/kg), TS-27 (15 mg/kg) and ISO-31 (25 mg/kg) derivatives of 1,2,3-triazoles were administered to alloxan diabetes mice for 10 days on a “per os” method. TF-25, TS-27, and ISO-31 triazole derivatives reversed body weight loss in rats in alloxan diabetes. New TF-25, TS-27, and ISO-31 derivatives of 1,2,3-triazole reduced the increase in plasma triglycerides and total cholesterol in diabetics. It was found that by increasing the amount of insulin, its secretion was restored. The new TF-25, TS-27, and ISO-31 derivatives of 1,2,3-triazole restored the activity of the enzymes SOD and catalase, which had decreased antioxidant activity in the liver homogenate of rats in alloxan diabetes. In diabetes mellitus, the LPO product in liver homogenate inhibited the intensity of MDA formation, the new TF-25, TS-27 and ISO-31 derivatives of 1,2,3-triazole.